CEO Compensation: A Brief Study from Indonesia - Wulandari Harjanti; Ali Farhan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Each country has different characteristics regarding the organizational behavior of its executives; Japan, Sweden, America, Norway and other countries have different patterns of compensating CEOs. This article is intended to explain the relationship between financial performance (ROE and ROA) and non-financial variables (Family ownership and CEO Power) on CEO compensation. The sample used in this research is 41 companies listed on the Indonesian stock exchange in 2017 – 2019. The method used is quantitative with multiple regression analysis. The results of the analysis show that ROE, Family Ownership, and CEO Power have a positive and significant effect on CEO Compensation, while ROA has a negative and significant effect on CEO Compensation.